ANALYSIS OF SUPPLY CHAIN FINANCING IN IMPROVING COMPANY FINANCIAL FLOW (STUDY OF DEBTORS OF BANK BRI KANCA SURABAYA RAJAWALI) - Rosyita, Amrina (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
Every company that wants to achieve the goal of getting optimal profits and reducing expenses as much as possible, such as spending on product marketing costs in the form of product design, forecasting needs, material procurement, production, inventory control, storage, and distribution to distributors, it is necessary to control costs through a production and information flow management model, especially in marketing a product by modifying logistics and financial management called supply chain financing. Currently, PT Bank Rakyat Indonesia Tbk is growing rapidly with various financial services offered to customers such as supply chain financing. Customers who currently have utilized the supply chain financing service program at one of BRI Branch Offices, namely BRI Surabaya Rajawali, including PT Envira (EV), PT Global Karya Utama (GK), PT Karya Usaha Baru (KU), PT Aryana Cakasana (AC), and PT Srikaya Putra Mas (SP). The purpose of this study is to analyze the financial flow condition of PT Envira (EV), PT Global Karya Utama (GK), PT Karya Usaha Baru (KU), PT Aryana Cakasana (AC), and PT Srikaya Putra Mas (SP) before and after implementing supply chain financing, and to analyze its effectiveness in improving financial flow capability. After an in-depth analysis, it is concluded that the Supply Chain Financing Account Receivable (SCF A/R) financing has been effective in EV, GK, AC, and SP companies but less effective in KU company due to internal company factors where PT Sinarmas Group transferred its project to another subsidiary which is also engaged in security services (Security) so that the Net Income of KU company decreased even though it had received Supply Chain Financing Account Receivable (SCF A/R).